RNA secondary structure profiling in zebrafish reveals unique regulatory features - Kaushik, Kriti; Sivadas, Ambily; Vellarikkal, Shamsudheen Karuthedath; Verma, Ankit; Jayarajan, Rijith; Pandey, Satyaprakash; Sethi, Tavprithesh; Maiti, Souvik; Scaria, Vinod; Sivasubbu, Sridhar (BMC genomics, 2018)
Background RNA is known to play diverse roles in gene regulation. The clues for this regulatory function of RNA are embedded in its ability to fold into intricate secondary and tertiary structure. Results We report the transcriptome-wide RNA secondary structure in zebrafish at single nucleotide resolution using Parallel Analysis of RNA Structure (PARS). This study provides the secondary structure map of zebrafish coding and non-coding RNAs. The single nucleotide pairing probabilities of 54,083 distinct transcripts in the zebrafish genome were documented. We identified RNA secondary structural features embedded in functional units of zebrafish mRNAs. Translation start and stop sites were demarcated by weak structural signals. The coding regions were characterized by the three-nucleotide periodicity of secondary structure and display a codon base specific structural constrain. The splice sites of transcripts were also delineated by distinct signature signals. Relatively higher structural signals were observed at 3’ Untranslated Regions (UTRs) compared to Coding DNA Sequence (CDS) and 5’ UTRs. The 3′ ends of transcripts were also marked by unique structure signals. Secondary structural signals in long non-coding RNAs were also explored to better understand their molecular function. Conclusions Our study presents the first PARS-enabled transcriptome-wide secondary structure map of zebrafish, which documents pairing probability of RNA at single nucleotide precision. Our findings open avenues for exploring structural features in zebrafish RNAs and their influence on gene expression.